Policies and Responsibilities of Government Officials during the Covid-19: The Problem of Interpreting the Phrase of Good Faith in Law Number 2 of 2020 - Achmad Dardiri Hasyim; Mufrod Teguh Mulyo; Darsinah Darsinah (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2022)
Abstract: Article 27 Paragraph (2) Law Number 2 of 2020 introduces the term